Legal Protection for Limited Liability Company against Self-Dealing by Boards of Directors - Ery Arifudin; Ramadhio Adi Prasetyo (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
The Law Number 40 of 2007 Concerning Limited Liability Companies does not clearly forbid self-dealing transactions by the Board of Directors of Limited Liability Companies. The Board of Directors has a chance to engage in self-dealing activities that are fraught with conflicts of interest if this ban doesn't exist, which could be detrimental to the company. The study is aimed at analyzing the legal safeguards for limited liability companies against the self-dealing activities of board of director members and the board's accountability for such activities that result in losses for limited liability companies. Legal, conceptual, and case-based research methods are combined to create normative legal research. Interviews, literature reviews, and document studies as data collection methods were used. This study concludes that the Law does not specifically forbid limited liability company board of directors self-dealing transactions. The availability of provisions in Book III of the Civil Code as lex generalist, the Limited Liability Companies Law itself as lex specialist, and the principles of Good Corporate Governance all provide legal protection for limited liability businesses from self-dealing transactions. Restrictively, the Law gives the Board of Directors, Board of Commissioners, and Shareholders the right to sue the Board of Directors in district court for any wrongdoing caused by the Board of Directors.